2017
DOI: 10.18488/journal.107.2017.51.56.69
|View full text |Cite
|
Sign up to set email alerts
|

Is Marketing Limited to Promotional Activities? The Concept of Marketing: A Concise Review of the Literatur

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On the other hand, this results not consistent with Valmohammadi and Ghassemi (2016), in Iranian they discovered that, there is no link between implementation of reward and recognition programs and work success because of the most significant being resources and organizational culture .The finding of the current study differs from those of Waheed, Yang, Ahmed, Rafique, and Ashfaq (2017), in Lahore, Pakistan they found that, no relation between workers perception and internal marketing promotional activities this is due to must considering a variety of factors including internal marketing philosophy, providing resources.…”
Section: Disscusioncontrasting
confidence: 87%
“…On the other hand, this results not consistent with Valmohammadi and Ghassemi (2016), in Iranian they discovered that, there is no link between implementation of reward and recognition programs and work success because of the most significant being resources and organizational culture .The finding of the current study differs from those of Waheed, Yang, Ahmed, Rafique, and Ashfaq (2017), in Lahore, Pakistan they found that, no relation between workers perception and internal marketing promotional activities this is due to must considering a variety of factors including internal marketing philosophy, providing resources.…”
Section: Disscusioncontrasting
confidence: 87%
“…Research of Al-Ghaswyneh [1] analyzed the perception of prices, rewards, social network posts, and online reviews as consumer behavior influences, where they proved that rewards have the greatest influence on purchases. Studies conducted by Chowhury et [29][30][31] have demonstrated the effect of prices on consumer behavior, where consumers were in a position to bargain for a price and decide on which product to buy considering the price and quality of the product. Svatosova [32] stated in her research that consumers are mostly facing challenges which will affect them emotionally and psychologically.…”
Section: Consumermentioning
confidence: 99%
“…Studies of Al-Salamin et al; Aschemann-Witzel et al; and Waheed et al [29][30][31] have demonstrated the effect of prices on consumer behavior, where consumers were in a position to bargain for a price and decide on which product to buy considering the price and quality of the product. Svatosova [32] stated in her research that consumers are mostly facing challenges which will affect them emotionally and psychologically.…”
Section: Research Objectives and Hypothesismentioning
confidence: 99%
“…In turn, the marketing manager will distribute the resources available among the various competing marketing mix instruments. This would continue to instill the company's marketing philosophy in this way (Waheed et al, 2017).…”
Section: Introductionmentioning
confidence: 96%